2012
DOI: 10.1177/0018726711431351
|View full text |Cite
|
Sign up to set email alerts
|

Doing what she thinks is best: Maternal psychological wellbeing and attaining desired work situations

Abstract: In this study we explore the gap between preferred and actual work situations for mothers of young children. We further examine the effects of not meeting desired work situation preferences on mothers' depression and parenting stress over time. Using data from the National Institute of Child Health and Human Development's Study of Early Child Care (1141 families) our findings indicate up to 71 percent of mothers in this sample did not achieve their preference. After controlling for marital status, ethnicity, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 43 publications
(41 reference statements)
0
28
0
Order By: Relevance
“…Even mothers who do not desire employment may accrue mental health benefits from paid employment, at least if they acquire high quality jobs (Usdansky et al 2012). Leaving paid work may thus have far-reaching and negative long-term consequences for these mothers in terms of both financial and labour market matters as well in terms of health and well-being—of relevance to themselves (Ahrens and Ryff 2006; Bailey et al 2007; Holmes et al 2012; Munk-Olsen et al 2006), their child (McMunn et al 2010) and the work place (Hill and Weiner 2003; Mainiero and Sullivan 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Even mothers who do not desire employment may accrue mental health benefits from paid employment, at least if they acquire high quality jobs (Usdansky et al 2012). Leaving paid work may thus have far-reaching and negative long-term consequences for these mothers in terms of both financial and labour market matters as well in terms of health and well-being—of relevance to themselves (Ahrens and Ryff 2006; Bailey et al 2007; Holmes et al 2012; Munk-Olsen et al 2006), their child (McMunn et al 2010) and the work place (Hill and Weiner 2003; Mainiero and Sullivan 2005). …”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have documented that incongruence between mothers' attitudes or desired employment status and actual employment are associated with reductions in subjective well-being or increased depressive symptoms (Berger, 2009;Klein et al, 1998;Holmes et al, 2012). More widespread availability of state subsidized day-care provision may imply more flexible options in combining different types of work and care arrangements with potential positive consequences for parental -in particular maternal -well-being.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…On the other hand, they may also miss out on some of the benefits of employment, such as an enriched identity, social support, and increased income (Barnett & Hyde, 2001). Consistent with this latter possibility, a recent study found that stay-at-home moms who wanted to work outside the home showed higher rates of depression than working moms or stay-at-home moms who embraced their role (Holmes, Erickson, & Hill, 2012). By contrast, stay-at-home dads reported generally relatively high levels of life satisfaction (Rochlen, McKelley, Suizzo, & Scaringi, 2008).…”
mentioning
confidence: 95%